Design of immersive virtual reality training for endoscopic surgery - Pumarejo Mercado, Fuad Antonio; Fontana Catapán, Márcio (Arcos Design, 2023)
Endoscopic surgery training is limited by a lack of specialized instructors and access to technological equipment. Virtual reality training offers a solution to this issue, as it allows for accessible and efficient practice. This study conducts a literature review to investigate the current state of virtual reality training systems in endoscopic surgery and subsequently designs and tests an immersive virtual reality system through a proof of concept with endoscopic surgery specialists.